Design charts for rectangular R/C columns under biaxial bending: A historical review toward a Eurocode-2 compliant update. (15th May 2016) - Papanikolaou, Vassilis K.; Sextos, Anastasios G.
Graphical abstract: Highlights: New series of Eurocode-2 compliant design charts for rectangular columns under biaxial bending. Rigorous validation through back-analysis and comparisons to previous chart implementations. Unprecedented vector graphics quality and output detail. Full chart set for various material grades and reinforcement arrangements available online. Abstract: The objective of this paper is to review the historical context of design charts for rectangular reinforced concrete columns under biaxial bending, critically assess their evolution in time and provide a new series, compliant to the latest draft of Eurocode 2. The motivation for such a development arises from the different assumptions and recommended values prescribed in the respective National Annexes of individual countries that use the Eurocodes, which essentially yield impossible to design without the aid of specialized, typically commercial, computer codes. Along these lines, a new extensive design chart dataset of unprecedented output quality is made available herein that covers both normal and high-strength concrete as well as different steel grades. The dataset developed is fully validated against conventional procedures while the error induced in design by the use of older design aids is comparatively assessed, clearly highlighting the necessity for a new design charts dataset at least under certain loading and reinforcement configurations. The present charts are expected to provide a valuable tool for the professional community, facilitate the use of Eurocodes and minimize the epistemic uncertainly associated with the use of older or incompatible design charts in the design of reinforced concrete members.